Abnormal Network Homogeneity in the Right Superior Medial Frontal Gyrus in Cervical Dystonia - Wei, Shubao; Chen, Xiuqiong; Xiao, Yousheng; Jiang, Wenyan; Yin, Qiong; Lu, Chunhui; Yang, Lu; Wei, Jing; Liu, Yang; Li, Wenmei; Tang, Jingqun; Guo, Wenbin; et al. (Frontiers in Neurology, 2021)
Background: Increasing evidence from modern neuroimaging has confirmed that cervical dystonia (CD) is caused by network abnormalities. Specific brain networks are known to be crucial in patients suffering from CD. However, changes in network homogeneity (NH) in CD patients have not been characterized. Therefore, the purpose of this study was to investigate the NH of patients with CD. Methods: An automated NH method was used to analyze resting-state functional magnetic resonance (fMRI) data from 19 patients with CD and 21 gender- and age-matched healthy controls (HC). Correlation analysis were conducted between NH, illness duration and symptom severity measured by the Tsui scale. Results: Compared with the HC group, CD patients showed a lower NH in the right superior medial frontal gyrus. No significant correlations were found between abnormal NH values and illness duration or symptom severity. Conclusion: Our findings suggest the existence of abnormal NH in the default mode network (DMN) of CD patients, and thereby highlight the importance of the DMN in the pathophysiology of CD.